The Impact of Mobile Phone Use on Early Childhood Interaction And Behavior Patterns: A Qualitative Study - Soniati, Nia (CV. Chandralia Bintang Pustaka, 2026)
Mobile phone use among young children is increasing along with the development of digital technology and has become a serious concern in education. This study aims to determine the impact of mobile phone use on the interaction and behavior patterns of young children and to identify the role of teachers in addressing this issue in preschool settings. This research uses a qualitative approach with a phenomenological paradigm. The research participants were ten PAUD teachers in Sukabumi Regency who were selected using a purposive sampling technique. Data collection was conducted from January to March 2026 using structured interviews. The data obtained were analyzed using thematic analysis techniques to identify key patterns and themes. The results showed that mobile phone use impacts the quality of children's social interactions, reduced verbal communication, and the emergence of changes in behavior and emotional regulation, such as irritability and impatience. This study also found that teachers have a fundamental role in minimizing the negative impacts of mobile phone use through social interaction-based learning strategies, group games, and restrictions on digital media use in schools. Furthermore, collaboration between teachers and parents is a key factor in successfully addressing the impacts of mobile phone use on early childhood . This research provides theoretical and practical contributions to the development of early childhood education in the digital era.